Kepuasan Konsumen Mitsubishi Xpander Melalui Mediasi Keunggulan Bersaing (Studi Pada Konsumen PT. Borobudur Otto Mobil Semarang) - Bawono, Reza Luthfi; Indarto, Indarto; Budiati, Yuli (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study aims to evaluate the impact of innovation, product differences, and brand perception on Mitsubishi XPander buyer satisfaction in Semarang, both directly and through competitive advantage as a mediator. This research is a type of explanatory research with primary data. The population of this study are consumers who have purchased Mitsubishi XPander in Semarang, with a sample of 138 respondents, selected through purposive sampling method. Data were collected through questionnaires and analyzed using a Structural Equation Model (SEM) based on Partial Least Square (PLS). The results showed that product innovation, product difference, and brand perception positively and significantly affect competitive advantage. In addition, product innovation, product difference, brand perception, and competitive advantage also positively and significantly affect buyer satisfaction. The results of the mediation analysis show that competitive advantage mediates the relationship between product innovation and buyer satisfaction, product differences and buyer satisfaction, and brand perception and buyer satisfaction.